Characterization of Biosorbent from Musa acuminata balbisian Peel using FTIR Spectroscopy and Its Application to Cadmium (Cd) Removal: Effect of Activator Type, pH, and Biosorbent Ratio - Lia Cundari; Alna Livia Fanneza; Nanda Citra Arisma (CHEMICA: Jurnal Teknik Kimia, 2022)
Biosorbent that use in this study made from kepok banana peel (Musa Acuminata balbisian). The present study is done to determine the characteristic of biosorbent and the effect of activator type, pH, and ratio of biosorbent for the cadmium removal. The experiments were carried out in batch process, laboratorium scale, room temperature, and 60 mesh of biosorbent size particle. The biosorbent produced by using chemical activation method onto dry banana peel. The variation in this research was the type of activator (H3PO4 and H2SO4), pH of Cadmium (3, 4, and 5), and the ratio of biosorbent dosage to the volume of cadmium solution (1:20, 1.5:20, and 2:20 (g/ml)).  The biosorbent characterized by using Fourier Transform Infra-Red (FTIR). The cadmium concentration analyzed by using Atomic Absorption Spectroscopy (AAS). Characterization with FTIR showed the differences in functional groups onto biosorbent before and after adsorption. There was a change in the spectral band of C-H and C=O functional groups for biosorbent that activated with H3PO4 and a change in the spectral band of C-H functional groups for biosorbent that activated with H2SO4. The acid activators showed the best condition was at 90 minutes contact time, pH 4 and the ratio of biosorbent dosage and the volume of 1.5:20 (g/ml). The result showed that the H3PO4 was the best acid activator in the removal of cadmium with amount of 99.91%.